The Influence Of Application Of Problem Based Learning(PBL)Learning Model On The Ability To Think Student Criticism In Class V Thematic Lessons UPT SPF SD Inpres Rappokalling 1 Tallo District,Makassar City - Mutmainnah, Mutmainnah; Achmad, Widya Karmila Sari; Tati, Andi Dewi Riang (International Journal of Elementary School Teacher, 2024)
This research aims to determine the description of the application of the problem based learning model in Thematic learning , the description of students' critical thinking abilities in Thematic lessons and determine the influence of the application of the problem based learning model on students' critical thinking abilities in Thematic subjects in class V UPT SPF SD Inpres Rapokalling 1 Tallo District, Makassar City . The method used in this research is the Quasi Experimental Design Approach. Quasi experimental design. The population in this study were all class V students of UPT SPF SD Inpres Rapokalling 1, Tallo District, Makassar City and the research sample was 27 class VA students. The sampling technique is random sampling. The instruments used were non-tests (observation sheets) and written tests (pretest and posttest) totaling 10 questions (multiple choice) and 5 questions (description) of the LKPD. The research results showed that the tcount value was 677 with a significance level of α=0.05 and the ttable was 2.021, so tcount > ttable = 677 > 2.021, so Hi was accepted. So it can be concluded that the application of Problem Based Learning in class V UPT SPF SD Inpres Rapokalling 1 Tallo District Makassar City was implemented well and carried out according to the appropriate stages and had a positive influence. This is proven by the results of observations made at each meeting which have increased from good to very good category. Through this learning model, students will begin to be trained to develop creativity, imagination, innovation, expression, and be actively involved in the learning process, thus having an impact on students' critical thinking abilities.This research aims to determine the description of the application of the problem based learning model in Thematic learning , the description of students' critical thinking abilities in Thematic lessons and determine the influence of the application of the problem based learning model on students' critical thinking abilities in Thematic subjects in class V UPT SPF SD Inpres Rapokalling 1 Tallo District, Makassar City . The method used in this research is the Quasi Experimental Design Approach. Quasi experimental design. The population in this study were all class V students of UPT SPF SD Inpres Rapokalling 1, Tallo District, Makassar City and the research sample was 27 class VA students. The sampling technique is random sampling. The instruments used were non-tests (observation sheets) and written tests (pretest and posttest) totaling 10 questions (multiple choice) and 5 questions (description) of the LKPD. The research results showed that the tcount value was 677 with a significance level of α=0.05 and the ttable was 2.021, so tcount > ttable = 677 > 2.021, so Hi was accepted. So it can be concluded that the application of Problem Based Learning in class V UPT SPF SD Inpres Rapokalling 1 Tallo District Makassar City was implemented well and carried out according to the appropriate stages and had a positive influence. This is proven by the results of observations made at each meeting which have increased from good to very good category. Through this learning model, students will begin to be trained to develop creativity, imagination, innovation, expression, and be actively involved in the learning process, thus having an impact on students' critical thinking abilities.